Identification of differentially expressed mRNAs in human fetal liver across gestation. - Malhotra, K (1999)
Differential gene expression, with its precise start and stop times, is believed to be critical for the programmed development of new cells and tissues. Within the developing fetus, one tissue of particular interest is fetal liver. This organ undergoes rapid changes in the pathway toward liver development in utero since it is also the major site of hematopoiesis, until bone marrow hematopoiesis predominates. Believing that patterns would emerge from the bi-weekly large-scale inspection of expressed genes in the fetal liver, we employed differential display reverse transcription-polymerase chain reaction (DDRT-PCR) as ourprimary inspection tool. Using DDRT-PCR, we isolated cDNAs differentially expressed throughout fetal liver development and in adult liver. We displayed approximately 25 000 cDNAs from 10 and 24 week fetal liver and adult liver. From this initial screen, we determined that approximately 0.1-1% of the mRNA population undergoes expression changes. We extracted, purified and sequenced 25 differentially displayed cDNA bands. Fourteen cDNAs had similarities to known genes, while 11 cDNAs were not similar to any characterized gene. The differentially expressed cDNAs from known genes present in fetal liver include alpha-fetoprotein, stem cell factor, erythroid alpha-spectrin, 2,3-bisphosphoglycerate mutase, insulin-like growth factor-2, porphobilinogen deaminase and Mac30. The differentially expressed cDNAs present in adult liver but not in 10 week fetal liver were nicotinamide deaminase, human fibrinogen-related protein and alpha-acid glycoprotein. The majority of differentially expressed genes found during this effort appear to be turned on during organogenesis, however, some genes were found that are apparently turned off completely.